Isolation and characterization of bamA genes, homologues of the γ-butyrolactone autoregulator-receptor gene in Amycolatopsis mediterranei, a rifamycin producer - Aiyada Aroonsri (2018)
Four genes (bamA1, bamA2, bamA3 and bamA4) encoding homologues of the γ-butyrolactone autoregulator receptor of Streptomyces were found and cloned from Amycolatopsis mediterranei, a typical non-Streptomyces actinomycetes and a producer of rifamycin, one of the major anti-tuberculosis drugs in clinical treatment. Transcriptional analysis demonstrated that bamA1 and bamA2 are transcribed in a growth-dependent manner, while bamA3 and bamA4 are constitutively transcribed during growth. Binding assays using3H-labeled autoregulator analogues as ligands confirmed that all of the recombinant BamA proteins expressed in Escherichia coli have clear binding activity toward several types of Streptomyces autoregulators. The ligand specificity of the recombinant BamA1 protein was identical to that of the crude cell-free lysates of A. mediterranei reported in our previous work. These results suggest that A. mediterranei, which is phylogenetically situated in a distal clade from the genus Streptomyces as non-Streptomyces actinomycetes, has an autoregulator-mediated signaling system. © 2008 Springer Science+Business Media B.V.